Perceptions of risk and outbound tourism travel intentions among young working Malaysians - Lim, Khong Chiu; Cheah, Swee Ting; Alananzeh, Omar A.; Khor, Poy Hua (University of Jordan, 2019)
Understanding risk and how it is perceived is a crucial step in predicting travel intentions. The purpose of this study is to examine the relationship between risk perceptions and travel intentions associated with an outbound tourism among young Malaysians. Young adults aged between 21 to 35 years old were involved in this study. This study was part of a larger study that explores factors affecting the intention to travel overseas. A quantitative approach was employed and a structured questionnaire was administered to 570 respondents who were selected through a cluster random sampling technique. Data were collected from young Malaysians who work in public and private sectors. Research respondents responded to a questionnaire designed to measure perceived risks, outbound travel intentions and socio-demographics.Particularly, the results indicate that the intention of young Malaysians to take a holiday overseas within the next year was very high. The regression analyses revealed that physical risk, financial risk and psychological risk had significantly negative impacts on respondent’s intention to travel overseas. However, performance risk had positive significant influence on young Malaysians to travel overseas. This study is helpful for marketers in developing positioning strategies in order to provide a total tourism experience for the potential travellers.